A safety lancet for neonatal blood spot tests: a design that facilitates pain-free, atraumatic samples. (24th January 2019) - Goodwin, Sarah; Supachana, Nichole
Abstract : Safety lancets are used to collect capillary blood samples to test if neonates have rare but serious congenital conditions, such as sickle cell disease, cystic fibrosis, congenital hypothyroidism and inherited metabolic diseases. Blood samples are taken from the heel, but the procedure can cause the neonate pain or discomfort, as well as a risk of local trauma to the nerves and blood vessels, bleeding, infection and scarring. This article explores the need for blood sampling in neonates, discusses the procedure and outlines the types of lancets available. It describes the Neoheel Safety Lancet (Smiths Medical), whose features are designed to avoid pain and trauma during the procedure. Three case studies are included to describe its use in clinical practice.